Pillars in children’s learning - Sachica Velazco, Laura Susana; Peña Herrera, Elsida; Valdelamar Zafra, Liliam Patria (Rastros Rostros, 2002)
Art and play in the educational environment allow children to learn about their daily lives, situations and experiences such as the beauty of a sunrise, the colorful rainbow, the beauty of a musical composition, the deafening noise produced by automobile traffic, the melancholy of a rainy afternoon; to contrast aesthetic experiences of their daily lives, to perceive, assimilate and be aware of the impact of sensations that open their sen